Architecture in uniform designing and building for the Second World War - Cohen, Jean-Louis (Canadian Centre for Architecture, 2011)
Offers a fresh perspective on the architectural history of the Second World War, which in previous accounts has most often been viewed as a hiatus between peaceful periods of production. This title focuses on plans, buildings, and technological inventions but also examines the many types of visual representation used for war purposes.